The role of Hydrogen as a temporary alloying element during the manufacturing stages of Ti-6AI-4V by the powder metallurgy route - Mariaye, Marie Mellisa Sandy (Department of Mechanical Engineering, 2020)
The aim of this research was to investigate the effects of using hydrogen as a temporary alloying element in the manufacturing of titanium (Ti) and Ti-6Al-4V by the powder metallurgy (PM) route using commercially pure titanium (CP Ti), titanium hydride (TiH2) and Ti-6Al-4V powders as starting materials. Several powder blends were selected and respective samples were pressed at compaction pressures ranging from 300-500MPa for green density and strength measurements. It was found that the higher the level of TiH2 in the powder blend, the lower the green density and strength. However, powder blends containing more than 40wt% of TiH2 did not result in considerable decrease in green strength and density. The selected powder blends underwent thermal decomposition analysis. The results show that hydrogen introduction is more beneficial in the form of a hydrogen atmosphere rather than using TiH2. Samples of selected powder blend were pressed and sintered at 1050°C under argon and partial hydrogen atmospheres. While the general trend was that sintered densities improved with TiH2 content as well as in the presence of hydrogen in the sintering atmosphere, there was an unexpected decrease from green to sintered density for the TiH2-6Al-4V samples sintered in partial hydrogen at 1050°C. These results were supported by the microstructural analysis. Additional sintering trials for CP Ti-6Al-4V and TiH2-6Al-4V for different sintering conditions were also conducted and their relative sintered densities were concurrent with the density results obtained in the current literature (>97%). Elemental mapping conducted proved that the diffusion of the MA particles were the same for both TiH2-6Al-4V and CP Ti-6Al-4V. The decrease from green to sintered density in the TiH2-6Al-4V samples was due to the formation and trapping of H2O (g). At 1050°C the rate of H2 and subsequent H2O gas release is lower as compared to 1200°C. Hence, H2O gas molecules are trapped for longer causing the formation of larger pores that are harder to shrink especially at 1050°C. In a negative pressure atmosphere like vacuum, the higher pressure gradient between sample and atmosphere will favour faster diffusion rate of H2O gas which prevents big pore formation thus favouring faster densification. Sintering TiH2 based compacts in a partial hydrogen atmosphere has not proven to be very beneficial in aiming to decrease the sintering temperature.